False Memories for Affective Information in Schizophrenia - Fairfield, Beth; Altamura, Mario; Padalino, Flavia A.; Balzotti, Angela; Di Domenico, Alberto; Mammarella, Nicola (Frontiers in Psychiatry, 2016)
Studies have shown a direct link between memory for emotionally salient experiences and false memories. In particular, emotionally arousing material of negative and positive valence enhanced reality monitoring compared to neutral material since emotional stimuli can be encoded with more contextual details and thereby facilitate the distinction between presented and imagined stimuli. Individuals with schizophrenia appear to be impaired in both reality monitoring and memory for emotional experiences. However, the relationship between the emotionality of the-to-be-remembered material and false memory occurrence has not yet been studied. In this study, twenty-four patients and twenty-four healthy adults completed a false memory task with everyday episodes composed of 12 photographs that depicted positive, negative or neutral outcomes. Results showed how patients with schizophrenia made a higher number of false memories than normal controls (p<0.05) when remembering episodes with positive or negative outcomes. The effect of valence was apparent in the patient group. For example, it did not affect the production causal false memories (p>0.05) resulting from erroneous inferences but did interact with plausible, script consistent errors in patients (i.e. neutral episodes yielded a higher degree of errors than positive and negative episodes. Affective information reduces the probability of generating causal errors in healthy adults but not in patients suggesting that emotional memory impairments may contribute to deficits in reality monitoring in schizophrenia when affective information is involved.